Identification and molecular mapping of Flowering Date1 (FD1), a major photoperiod insensitivity gene in the adzuki bean (Vigna angularis). (15th September 2016) - Yamamoto, Hiroki; Horiuchi, Yuki; Ogura, Reina; Sakai, Hiroaki; Sato, Hitoshi; Kato, Kiyoaki
Abstract: The induction of flowering under long‐day conditions is an important adaptation by short‐day plants, such as adzuki beans ( Vigna angularis ), to high‐latitude environments. This study clarified the genetic control underlying the long‐day insensitivity of adzuki bean cultivar 'Shumari'. 'Shumari' was found to be insensitive to a 16‐h day, whereas landrace Acc2265 was highly sensitive. When grown under natural long‐day conditions at Obihiro (42°9′N), Acc2265 initiated flowering at least 80 days after 'Shumari'. When 86 recombinant inbred lines (RILs) derived from crosses between 'Shumari' and Acc2265 were grown under these conditions, their flowering dates ranged from the middle of July to the end of October. The distinct bimodal distribution in the RIL population was due to a single major gene, designated Flowering Date1 ( FD1 ). Molecular mapping showed that FD1 was located between the SSR markers Az02‐37M3 and Az02‐40M9, at distances of 6 and 10.4 cM, respectively, on linkage group 2. RILs carrying FD1 S lacked long‐day sensitivity, whereas RILs carrying FD1 A were sensitive to long‐day conditions, confirming that FD1 controls long‐day sensitivity.